A review on the current developments in continuous lactic acid fermentations and case studies utilising inexpensive raw materials. (April 2019) - López-Gómez, José Pablo; Alexandri, Maria; Schneider, Roland; Venus, Joachim
Graphical abstract: Highlights: Lactic acid can be efficiently produced in continuous mode. Production of lactic acid in continuous mode eliminates product inhibition problems, typical of batch mode. Cell recycle systems can lead to enhanced lactic acid productivities. Case studies using cheaper substrates are presented. Tapioca starch and acid whey are suitable substrates for lactic acid production. Abstract: The numerous applications of lactic acid have made it one of the most important platform chemicals and, for many years, its biotechnological production has been the topic of intensive research. Currently, most of the lactic acid is manufactured in batch mode; however, continuous mode could offer various advantages, especially in terms of productivity. This review provides a summary of the most recent studies on continuous lactic acid production. Potential advantages of continuous over batch mode, the improvements that high cell densities can represent, utilisation of low cost substrates and some economic aspects of continuous mode are discussed. The review is complemented by 3 experimental case studies utilising inexpensive substrates: tapioca starch hydrolysate, molasses combined with rapeseed meal hydrolysate and acid whey. In all cases, continuous cultivation was coupled with cell recycling using hollow-fibre membranes forl - ord -lactic acid production. Lactic acid productivities higher than 5 g l −1  h −1 and substrate conversion yields above 80% were achieved for all the cases. Final lactic acid concentrations were 50.3, 59.6 and 45.9 g l −1 for the tapioca starch hydrolysate, molasses and acid whey respectively. These results support the claim that continuous cultivation using cell recycling is a promising approach for high lactic acid productivities.